Aspirações adaptativas: modelo relacional de feedback de desempenho, nível de aspiração e postura de risco - Ubaldine, Diego Torquato (2022)
The main objective of this research is to identify the way in which the particular cognitive inclination of performance-oriented managers influences their perceptions about performance and, consequently, their aspiration levels and risk postures. To this end, scales were developed to measure perception of performance feedback, aspiration level and risk posture; relationships between perception of performance feedback and aspiration level were examined, as well as between perception of performance feedback and risk posture; and a theoretical structural model that relates these latent constructs was proposed and validated. By means of a literature review, hypotheses were formulated and their relationships illustrated through the proposed theoretical structural model. A cross-sectional survey method was employed. Data collection involved the application of a questionnaire answered by highranking leaders of organizations in the food sector. Contact with the respondents was made via a business social network, LinkedIn. The indicators that make up the data collection instrument were validated qualitatively, through face and content validity, and quantitatively, through preliminary exploratory analysis, correlation analysis, exploratory factor analysis, reliability analysis and, finally, a convergent validity. Data analysis was conducted using classical descriptive and predictive statistics techniques, as well as modern machine learning techniques. The results point to a significant difference in the way in which performance-oriented managers adjust their aspiration levels and risk postures when compared to those who do not have this orientation, thus revealing a conditioned decision-making behavior, and shedding new light on the determinants of aspiration levels and risk postures. This happens because those who possess this particular cognitive trait seek to prove their competence, therefore biasing their performance perceptions and, consequently, being more incisive in adjusting upwards their aspiration levels and less incisive in taking risk than those who do not have this specific feature. Evidences also point to a non-linear relationship between the variables involved in this research, which differs from the current theoretical body and reveals the need to use more robust methods when it comes to endeavors of this nature. From a practical standpoint, to possess knowledge about one’s own cognitive biases and how these influence one’s decisions constitutes the possibility of unraveling biased choices, which constitutes a step in the way of improving strategic decisions.